Validação de marcadores microssatélites derivados de regiões funcionais do genoma de aveia - Santos, Fabiana Fonseca dos (2010)
The understanding of the genetic structure of the oat species can be obtained with the use of microsatellite molecular markers which represent powerful tools in the investigation of genetic parameters. This study aimed to search the identification and characterization of microsatellite markers occurrence in oat through bioinformatics, describing the possible role of individual genes based on the genome of rice and Arabidopsis thaliana. For the development and validation of EST (Expressed Sequence Tags) primers, sequences were obtained from a public database. A total of 7632 oat contigs were obtained after eliminating the redundancy. To characterize SSR (simple sequence repeats) loci, the SSRLocator program was used. For the design of primers, the module containing the program Primer3 was used. A total of 58 primers were found, from which ten were selected for validation by polymerase chain reaction. Ten genotypes were used to assess polymorphism detection ability of primers. Polymorphism was observed in 80% of primers, whereas the rest showed monomorphic bands. The high genetic diversity revealed by microsatellite markers in this study may reflect a high genetic diversity within the germplasm of Avena sativa.